Actively promoting student engagement within an online environment: Developing and implementing a signature subject on ‘Contemporary Issues in Sex and Sexuality’ - Fletcher, Gillian; Dowsett, Gary; Austin, Lilian (Journal of University Teaching and Learning Practice, 2012)
La Trobe University is committed to improving the first year experience, and to developing its online teaching portfolio in response to increasing student demand. This article will acknowledge that these two objectives will remain contradictory if online learning systems are used predominantly as repositories of information with little thought given to their specific pedagogic possibilities. The article will then present a case study of an ‘Signature Subject’ that was developed to actively promote learner-material, learner-learner and learner-lecturer engagement in an entirely online environment, through use of synchronous and asynchronous sessions. Background to subject development will be provided, followed by discussion of challenges faced, responses to challenges and outcomes in terms of student response. The article will conclude by arguing that, as universities increase their use of online learning due to the changing university environment, this does not have to lead to reduced student engagement or poorer first year experiences.